DEVELOPMENT OF TOOLS OF FINANCIAL MANAGEMENT IN THE RUSSIAN UNIVERSITIES - V. I. Pyatanova; N. N. Shash (Вестник Российского экономического университета имени Г. В. Плеханова)
The article reveals features of usage of modern technologies of financial management in practice of public finance management. It defines the main objectives of financial management tools in public sector. It underlines the connection between the monitoring of quality of financial management in the budgetary sphere and budgetary policy implementation by ensuring control and accountability in public resources management. It proves the necessity to develop and enhance the specific system of assessment indicators when carrying out monitoring of quality of financial management in the organizations of the budgetary sphere. Examples of the indicators used when carrying out monitoring of quality of financial management of higher educational institutions are given. Based on the results of monitoring of quality of financial management of higher educational institutions the complex of problems in the sphere of management of finance of higher educational institutions is identified. Practical recommendations are offered for the most problematic areas of financial management of educational institutions, such as, strategic and operational management of expenses; system of financial planning, budgeting and control; information support of decision-making, liquidity management; financial risks management. Taking into consideration the leading foreign practice, the complex of actions has been developed, which would allow to significantly improve the quality of financial management in the Russian system of higher education.